Utilização de esgoto tratado em sistema de lagoas de estabilização como água de amassamento e cura de concreto - Silva, Jorge Luís Melo da (2008)
It was studied the feasibility here on a technical point of view, the use of a predominantly domestic sewage effluent comes from the treatment system for stabilising the lagoons of the CAGECE’s Station Treatment of Sewage, located in the city of Aquiraz-CE as moulding and curing water of concrete produced in the laboratory scale. In preliminary chemical analysis, the effluent analysis proved to be suitable for use in the production of concrete. The results for tests to determine the pH to 25°C, total solids, total iron, chlorides and sulfates soluble showed itself within the limits required. No significant difference was found between the results in the tests of time to handle with paste made of cement produced with the effluent analysis and those obtained with drinking water, according to the required limit of difference of 30min. Nor was detected significant difference between the results obtained in testing for resistance to compression of 07 and 28 days achieved with corpses-of-proof cylindrical shaped and cured with the effluent analysis and those obtained with drinking water, according to the required limit of difference of 10%. While the treated effluent had a distinctive smell not very pleasant, the portfolio of cement, concrete and produced the bodies proof-of-shaped unchanged against its perceived odor. It has been proved that, based on the standard requirements demanded by NM 137, the sewage effluent is considered appropriate for the proposed use.